2022
DOI: 10.1088/1361-648x/ac5a03
|View full text |Cite
|
Sign up to set email alerts
|

Inducing chiral superconductivity on honeycomb lattice systems

Abstract: Superconductivity in graphene-based systems has recently attracted much attention, as either intrinsic behavior or induced by proximity to a superconductor may lead to interesting topological phases and symmetries of the pairing function. A prominent system considers the pairing to have chiral symmetry. The question arises as to the effect of possible spin-orbit coupling on the resulting superconducting quasiparticle spectrum. Utilizing a Bogolyubov-de Gennes (BdG) Hamiltonian, we explore the interplay of differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In conclusion, we studied pairing in the EEDL and in the EHDL on the basis of the BdG equation. Both systems are connected by the duality relation (6). Although the systems have different quasiparticle modes in the presence of a domain wall, they have the same Josephson currents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we studied pairing in the EEDL and in the EHDL on the basis of the BdG equation. Both systems are connected by the duality relation (6). Although the systems have different quasiparticle modes in the presence of a domain wall, they have the same Josephson currents.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on layered chiral materials has revived the interest in this approach, in particular, for the special properties of zero‐energy (or mid‐gap) modes. [ 3–9 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional TSCs with nontrivial properties exhibit topological edge states (TESs) along their edges, as dictated by the well-established bulk-boundary correspondence (BBC) principle, which associates the topological invariant with the number of TESs [2,18]. However, recent research progress on topological materials has revealed the sensitivity and richness of the CN phase diagram to variations in the chemical potential (µ), magnetic field (V z ), and superconducting order parameter amplitude [19][20][21][22][23]. Furthermore, there is evidence of a mismatch between the CN and the number of TESs, indicating a deviation from the BBC principle [19,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research progress on topological materials has revealed the sensitivity and richness of the CN phase diagram to variations in the chemical potential (µ), magnetic field (V z ), and superconducting order parameter amplitude [19][20][21][22][23]. Furthermore, there is evidence of a mismatch between the CN and the number of TESs, indicating a deviation from the BBC principle [19,[21][22][23][24][25][26][27][28][29][30]. For example, 2 H b -stacked bilayer transition metal dichalcogenides and bilayer bismuth lattice considering on-site s-wave pairing with Kane-Mele type SOC strength 0.0075 eV or without SOC show the TSC phases with rich and high CNs up to 4 under various µ and superconducting order parameters, which do not strictly always contain the same number of TESs as the CNs [19,25,29].…”
Section: Introductionmentioning
confidence: 99%